Contextual Teaching and Learning in Islamic Education: A Comparative Study at Two Pesantren Based Schools - Adib Aqil Haidar (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
The Contextual Teaching and Learning (CTL) model emphasizes the integration of academic content with real-life contexts, allowing students to better comprehend and apply knowledge in their daily lives. This study adopts a qualitative approach with a comparative case study design at two pesantren-based junior high schools: SMP Islam Nurul Fattah and SMP Nurul Jadid. Data were collected through in-depth interviews, participatory observations, and document analysis, and were analyzed using Miles and Huberman’s interactive model. The findings reveal that CTL enhances students’ active participation in learning, fosters critical thinking and problem-solving skills, and promotes collaborative engagement. Consequently, CTL offers a promising pedagogical alternative for cultivating a more dynamic and interactive learning environment within Islamic-based educational institutions.